PANDEMI COVID-19 DAN ERA TATANAN KEBIASAAN BARU DALAM PERSPEKTIF PSIKOLOGI PARIWISATA - Ni Desak Made Santi Diwyarthi (JURNAL KEPARIWISATAAN, 2021)
The COVID-19 Pandemic, which has existed for almost two years, has had a major impact on human life and the world of tourism. The development of tourism has undergone major changes with the implementation of health protocol standards. This paper provides additional horizons of information regarding the COVID-19 pandemic and the new order of life, the New Normal Era, in the world of tourism. Since the pandemic has changed society’s habits, and life has become a new norm. This study uses qualitative research methods with literature studies on the psychological situation of tourism conditions that occur, especially in Bali.  The COVID-19 pandemic raises awareness of the importance of hygiene, health, and safety for the community. Hotel management obtained a certificate for cleanliness, health, safety, and environmental implementation. There are some local wisdoms, such as Sagilik Saguluk, Briuk Sapanggul, Briuk Sapanggul, Tri Hita Karana, and Desa Kala Patra, in society. The conclusion of this research is that the COVID-19 Pandemic has made the tourism world slump. It has to follow the strict health protocol standards as a New Normal Era.